Komparasi Praktik Sewa Rahim di Indonesia dan Iran dalam Perspektif Hukum Perdata dan Hukum Islam - Saskara Putri, Made Dinda; Mashudi, Marzyadiva Camila (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze the practice of surrogacy within the legal perspective of Indonesia through civil law and its comparison with Iran, the only Muslim country that legalizes such a practice. The research adopts a normative legal method, employing a problem-oriented approach through legal comparison by analyzing relevant laws and documents, such as Law Number 36 of 2009 on Health and the Civil Code (BW), which explicitly prohibits third-party involvement in assisted reproductive technologies, with criminal sanctions imposed on violators. Furthermore, the Indonesian Ulama Council (MUI) has issued a fatwa affirming that surrogacy contradicts Islamic principles, particularly in matters related to lineage (nasab) and the commodification of the human body. The findings reveal that surrogacy practices are not explicitly regulated in Indonesia and are deemed contrary to the prevailing legal, moral, and religious provisions. In contrast, Iran, as a Muslim country, regulates and legalizes surrogacy, providing legal protection to all parties involved. This study also underscores the urgency of establishing regulations in Indonesia to address the current legal vacuum while taking into account moral and normative aspects. In conclusion, this comparative analysis highlights significant disparities in the legal approaches toward surrogacy practices between Indonesia and Iran, along with the legal implications faced by couples seeking to have children through such methods in each respective jurisdiction.